Effect of coercive measures on treatment outcome in involuntarily admitted patients in Amsterdam - van der Post, L. F. M.; Nusselder, K. J.; Peen, J.; Nabitz, U.; Dekker, J. M. (Frontiers in Psychiatry, 2023)
Objective: The prevalence of involuntary admissions rose the last forty years in European countries, including the Netherlands. Involuntary admissions result in seclusion, physical restraint and forced medication in approximately 40% of patients. We looked at whether treatment outcomes differ in patients with and without coercive measures. Methods: Using The Health of the Nation Outcome Scales (HoNOS) to measure treatment outcomes, we studied the files of 786 patients admitted involuntarily to an Amsterdam clinic. We applied Generalised Linear Models to determine whether the use, or not, of coercive measures during treatment was associated with a difference in outcomes. Results: 19% of the cohort were secluded in a High Security Room (HSR); 24% were secluded in their own room and/or received forced medication. After adjustment for the influence of diagnosis, disorder severity (initial HoNOS score) and treatment duration, the HSR group had, on average, a HoNOS difference score that was 2.4 points lower than patients without coercive measures (CI -4.0--.8.; p .003). In the seclusion in own room group, this score was 2.6 points lower (CI -4.0.--1.1; p .001), corresponding to an effect size of .35 and .40 respectively. Conclusions: Seclusion, whether or not in combination with forced medication, was applied to two-fifths of patients. The HoNOS scores of the group without coercion improved by nearly two and a half points more on average than those of the two groups with coercion. A causal relationship between coercion and treatment outcome could neither be confirmed nor excluded on the basis of our results.In the closing decades of the last century, the prevalence of involuntary admissions rose in several European countries (1). That rise continued in the Netherlands between 2003 and 2017 (2) 1 .